1992
DOI: 10.1146/annurev.so.18.080192.001511
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Concept Over Time: Research Issues and Directions

Abstract: Although theoretical attention has been devoted to the situational variability of the self-concept, empirical investigations continue to rely on one-shot methodologies. Such efforts assume that data obtained through these methods can be generalized to other situations in the person's life, even to subsequent years or stages in the life course. Self-concept is a structural product of reflexive activity, but it is also susceptible to change as the individual encounters new roles, situations, and life transitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(137 citation statements)
references
References 75 publications
3
132
1
1
Order By: Relevance
“…Moreover, several studies have failed to find significant age differences, including Trimakas and Nicolay's (1974) study of individuals age 66 -88 years, Erdwins et al (1981) study of four cohorts ranging in age from 18 to 75 years, and Ryff's (1989) study comparing middleaged adults (mean age ϭ 50 years) and older adults (mean age ϭ 75 years). Reflecting the lack of consistency in previous findings, researchers reviewing the literature on self-esteem and aging have failed to reach consensus on whether self-esteem increases, decreases, or remains stable in old age (Bengtson, Reedy, & Gordon, 1985;Brandtstaedter & Greve, 1994;Demo, 1992). 1 Thus, further research is needed before any strong conclusions can be made about self-esteem change in adulthood and old age.…”
Section: Old Agementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies have failed to find significant age differences, including Trimakas and Nicolay's (1974) study of individuals age 66 -88 years, Erdwins et al (1981) study of four cohorts ranging in age from 18 to 75 years, and Ryff's (1989) study comparing middleaged adults (mean age ϭ 50 years) and older adults (mean age ϭ 75 years). Reflecting the lack of consistency in previous findings, researchers reviewing the literature on self-esteem and aging have failed to reach consensus on whether self-esteem increases, decreases, or remains stable in old age (Bengtson, Reedy, & Gordon, 1985;Brandtstaedter & Greve, 1994;Demo, 1992). 1 Thus, further research is needed before any strong conclusions can be made about self-esteem change in adulthood and old age.…”
Section: Old Agementioning
confidence: 99%
“…Second, the vast majority of existing studies have focused on age differences in self-esteem during childhood and adolescence, and only a handful of studies have examined the development of self-esteem during adulthood or old age. As Demo (1992) noted, "the research to date is extremely lopsided, with 12-and 13-year-olds forming the floor and 18-to 22-year-olds representing the ceiling of our convenience samples" (p. 323). These gaps in the research literature make any conclusions about change across much of the life span highly tenuous.…”
mentioning
confidence: 99%
“…According to Demo (1992), these are childhood (ages 2-11), adolescence (ages 12-18), young adulthood (ages 19-39), middle adulthood (ages 40-65) and late adulthood (ages above 65).…”
Section: Actual Agementioning
confidence: 99%
“…More than two decades ago, however, Demo (1992) indicated that the focus of self-concept related research had been too narrow (i.e., student samples of young adults), thus limiting the applicability of the outcomes to individuals in other life-stages. The field of psychology responded through a growing body of knowledge that considers a wider range of respondents, such as adolescents and other groups from early to late adulthood (e.g., Green et al 2012;Lodi-Smith and Roberts 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation